A history of female football fans - Hayward, T. (2002)
The article deals with the development of female fans in football (19thcentury, new ideals, increasing respectability, prejudice, post-second world war, the 1960s, the era of hooliganism, the FSA survey, the growing role of women in the game, the 1995 FA Carling Premier League fan survey, conclusions).